WITHDRAWN: Factors associated with receipt of second-line recurrent or metastatic cervical cancer treatment in the United States: A retrospective administrative claims analysis - Kalyani Sonawane; Tara Castellano; Christina Washington; Jie Ting; Andy Surinach; Carol Kirshner; Jagpreet Chhatwal; Turgay Ayer; Kathleen Moore (Gynecologic Oncology Reports, 2022)
This article has been withdrawn from this issue: please see Elsevier Policy on Article Withdrawal (http://www.elsevier.com/locate/withdrawalpolicy).This article has been withdrawn at the request of the editor and publisher. It is now available at https://doi.org/10.1016/j.gore.2022.101121The publisher regrets that an error occurred which led to the premature publication of this paper. This error bears no reflection on the article or its authors. The publisher apologizes to the authors and the readers for this unfortunate error.